Glass fibre reinforce polymer structural selection as concrete beam reinforcement - Mohd. Sam, Abdul Rahman (Faculty of Civil Engineering, UTM, 2003)
Fibre Reinforced Polymer (FRP) made of a combination of continuous fibre embedded in resin matrix is an advanced composite material that has been identified as a potential new construction material. Some of the advantages of FRP are high tensile strength, lightweight, non-magnetic and durable. Since it is a non-corrodible material it may be used as reinforcement in concrete member. This paper presents the performance of concrete beams reinforced with different types of glass Fibre Reinforced Polymer (GFRP) sections. Two concrete beams, 125x200x2400 mm, reinforced with GFRP I-section and GFRP plate were cast and tested to study their flexural behaviour. Comparison was made with a control beam on the aspect of ultimate load, load- deflection behaviour, load-reinforcement strain behaviour, and mode of failure. The experimental results show that beams reinforced with GFRP sections experienced lower load carrying capacity, lower stiffness, larger deflection and less number of cracks. The failure of the GFRP reinforced concrete beams was either by crushing of concrete at the compression zone or rupture of the GFRP reinforcement.